Characterization of thyme essential oil by NMR spectroscopy - Sampaio, C. I. (2019)
Essential oils are plants secondary metabolites, which are widely used in the perfumery, food and pharmaceutical industries. In general, volatile oils or essential oils are predominantly constituted by two or three components, mostly terpenic hydrocarbons and terpenoids. Thymus vulgaris L. (Lamiaceae) is native from the southern Europe and the Mediterranean, where it has been used since ancient times as a flavor ingredient in culinary. In addition to its use in foods, T. vulgaris is a well-known herbal medicine that has been used for thousands of years to treat alopecia, dental plaque, dermatophyte infections, bronchitis, cough, inflammatory skin disorders and gastrointestinal distress. The major constituents of commercial T. vulgaris essential oil are thymol (23%–60%), -terpinene (18%–50%), p-cymene (8%–44%), carvacrol (2%–8%), and linalool (3%–4%). T. vulgaris oil, as well as thymol, have shown antibacterial, antifungal, and anti-inflammatory effects, accounting for its the medicinal uses. Several chemotypes of thyme, based on essential oil compositions, have been established, including thymol, carvacrol, linalool, borneol, geraniol, sabinene hydrate, as well as a number of multiple-component chemotypes.1 The quality of essential oils has been widely evaluated by gas chromatography coupled to mass spectrometry (GC-MS) and gas chromatography equipped with a flame ionization detector (GC-FID). Typically, analysis by these techniques take around 90 min and this is a limiting factor in situations where time is determinant. The quantification of the major constituents of commercial essential oils is vital, because they are extracted from different sources and their price varies with their content. Unlike chromatography, nuclear magnetic resonance (NMR) spectroscopy is a quick and non-destructive method, and it does not require calibration curves. The NMR method allows simultaneous quantitation of many components using one internal standard and a single spectrum. Moreover, it is not necessary to employ a high purity internal standard similar to the analyte of interest for accurate quantification. In addition, NMR can be used for quantification of compounds that degrade at elevated temperatures, which cannot be determined by GC.2 The aim of this work was to characterize and quantify the major constituents of thyme essential oil using different NMR techniques. In a first approach, using 1H, 13C and 2D NMR, it was possible to identify the main compounds thymol, p-cymene and -terpinene, thought the observation of the aromatic (H 9-6 ppm) region. However, due to the extensive overlap of peaks in the other zones of the spectra, it was not possible to identify the multiple signals observed in these regions. Fractionation of the oil was then carried out by column chromatography and the characterization of the resulting fractions by the same techniques enabled the identification of a considerable number of other components such as linalool, myrcene, thymol methyl ether and carvacrol methyl ether. A quantitative method using 1H NMR, could be also implemented enabling to quantify almost all the constituents identified in the oil. This could be a powerful tool to perform a rapid assessment of the essential oils composition and to evaluate their stability.